Blowup criteria for strong solutions to the compressible Navier–Stokes equations with variable viscosity. (June 2016) - Cai, Xiaoyun; Sun, Yongzhong
Abstract: For the compressible Navier–Stokes equations with viscosity and heat conductivity coefficients possibly depending on the density or temperature, several blowup criteria are given to the local-in-time strong solutions. The proof is based on energy methods together with elliptic and parabolic estimates adopted to the present situation.